Improved stability criteria for piecewise affine systems based on partition- and vertex-dependent Lyapunov functions - Xu, Jun (2013)
In this paper, we present two improved stability criteria for a class of piecewise affine systems. First, by applying a partition-dependent Lyapunov function, we present a stability result based on copositive matrices which can be solved by the linear matrix inequality (LMI) technique. Second, to further reduce the conservatism of stability analysis, we construct a vertex-dependent Lyapunov function for each partition and show how to use Sum-of-Square (SOS) technique and Pólya's Lemma to calculate the corresponding Lyapunov matrices and hence assert the system stability.